Learners’ experiences in using moodle lesson and H5P interactive content in learning public speaking - Umi Kalsom, Masrom; Zailani, Jusoh; Mir, Kamran (Asociación Mexicana de Maestros de Inglés, MEXTESOL A.C., 2025)
The digitalization of teaching continues to shape its future, demanding continuing adaptation to its growing needs. To meet the evolving expectations, many online learning modules have been produced. Nonetheless, many fail to capture learners’ interest as they lack creativity since they contain lengthy texts and uninteresting explanatory videos. For these reasons, instructors utilize educational animation, which is widely available on platforms such as Moodle, to take advantage of the benefits of interactive content to keep learners interested. Despite the efforts taken by the instructors in including interactive content, it is uncertain what learners think of the content. This study aims to explore learners’ experience on the use of interactivity in Public Speaking Skills course using Lesson Activity and H5P Interactive Content features on Moodle. Sixty-three students participated in the study and completed the online survey at the end of the lessons. Participants were asked to rate the interactive activities and share their experiences on the use of the features in their lessons. This study shows that the majority of the participants had a positive experience with both interactive activities. This study is important as it provides information on how Moodle Lesson and H5P Interactive Content can be better adapted in the future for blended learning, online learning, or hybrid classrooms.